Implementasi Undang-Undang Nomor 13 Tahun 2022 Tentang Pembentukan Peraturan Perundang-Undangan terhadap Peraturan Daerah Kabupaten Karawang Mengenai Pemindahan Pedagang Kaki Lima Berdasarkan Asas Keadilan - Sanih, Sanih; Hidayat, Anwar; Abas, Muhamad (Wajah Hukum, 2024)
This study focuses on Article 31, Paragraph (1) regarding the analysis of the alignment between the Karawang Regency Regional Regulation No. 4 of 2015 on the Regulation and Empowerment of Street Vendors and Law No. 13 of 2022 on the Formation of Legislation. Street vendors have complained about the high cost of stalls in the new market, which was established by the Regent of Karawang based on the new regional regulation. The research method employed is a normative juridical approach, with a research plan spanning 5 months. The scope of the study includes the relocation and empowerment of street vendors. The legal materials used are secondary legal sources. This research provides recommendations for improving the implementation process and adjusting policies to ensure that the objectives of relocating street vendors are achieved fairly and efficiently. The findings offer insights into how the formation of legislation can be enhanced to better address the needs of street vendors.